Environmental Sustainable in Household Waste Management For Urban Resilience: Insight From Makassar City, Indonesia - Abdillah Abdillah (Dealings Foundation Institute, 2023)
This study only focuses on a small aspect of environmental protection, namely proper household waste management for urban resilience in Makassar City, Indonesia. This study discusses how household waste in Makassar City can be converted into useful products and economic value that will reduce waste generation and maintain the preservation of densely populated urban environments in Makassar City, Indonesia. This study methodology is qualitative with a case study approach in looking at environmental degradation caused by an increase in household waste generation in Makassar City which has an impact on the environment and socio-economic activities of Makassar City community. The results of this study indicate that the development of environmental problems in household waste management in Makassar City is still experiencing problems. So in good governance, it is driven by the helix innovation system which involves various stakeholders to turn household waste into useful products with economic value. The helix innovation system as a solution to the problem of increasing household waste in Makassar City utilizes Incineration Technology and the Waste Bank and Composting Innovation Program for organic waste as environmental preservation for densely populated cities in Makassar City, Indonesia which involves community groups. Wet household organic waste is made into compost which can be used in plantations and livestock. Waste management in Makassar City is regulated in Makassar Mayor Regulation No. 4 of 2011 concerning Waste Management and Makassar Mayor Regulation No. 35 of 2018 concerning Policies and Strategies for Household Waste Management and Household Waste.